2013
DOI: 10.1007/s10535-012-0282-0
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in molecular events of fruit abscission

Abstract: It is widely accepted that fruit abscission is a highly regulated developmental process that is both influenced and activated in response to changing environment and plays crucial roles in the health and reproductive success of plants. Recent evidences showed that numerous genes related to metabolic and signalling pathways were coordinately implicated in regulating fruit abscission. Cross talks within hormones, between saccharides and hormones, as well as between polyamines and ethylene result in synergetic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 63 publications
1
29
0
Order By: Relevance
“…However, our data demonstrated that gibberellin alone could not inhibit citrus fruitlet abscission, but IAA could (data not published). Recently, several reports also pointed out that flower or fruitlet abscission were significantly related to auxin (Blanusa et al 2005;Meir et al 2010;Xie et al 2013). These findings suggested that auxin was central to fruitlet abscission and some early auxin-responsive genes, principally GH3s, ARFs and AUX/ IAAs were involved in this physiological process.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, our data demonstrated that gibberellin alone could not inhibit citrus fruitlet abscission, but IAA could (data not published). Recently, several reports also pointed out that flower or fruitlet abscission were significantly related to auxin (Blanusa et al 2005;Meir et al 2010;Xie et al 2013). These findings suggested that auxin was central to fruitlet abscission and some early auxin-responsive genes, principally GH3s, ARFs and AUX/ IAAs were involved in this physiological process.…”
Section: Introductionmentioning
confidence: 96%
“…The second one, namely June drop, reduces the number of growing fruitlets from abscission zone C located between calyx and ovary which is gradually activated when AZ A progressively becomes inoperative. There are a few reports suggesting that hormones such as GA, IAA, CK, ABA and ethylene might play a decisive role in ovary abscission (Iglesias et al 2006;Xie et al 2013). Among those hormones mentioned above, GA is thought to be a pivotal effector that inhibits fruitlet abscission in citrus (Ben-Cheikh et al 1997;Ullah et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Like many other fruit-rotting fungi, diplodia has been reported to produce and secrete cell wall-digesting enzymes, including polygalacturonase, cellulase, and ␤-glucosidase (32)(33)(34)(35), similar to citrus enzymes involved in abscission (36)(37)(38). In addition, it has been reported that the increased activity of the cell wall-digesting enzymes was associated with increased incidence of SER (39).…”
mentioning
confidence: 99%
“…The second wave, namely June drop, reduces the number of growing fruitlets from abscission zone C located between calyx and ovary which is gradually activated when AZ A progressively becomes inoperative. A few reports suggested that hormones such as gibberellin (GA), indole-3-acetic acid (IAA), cytokinin (CTK), abscisic acid (ABA), and ethylene were cooperatively involved in ovary abscission (Iglesias et al 2006;Xie et al 2013). Recently, several reports pointed out that flowers or fruitlets abscission were significantly related to auxin (Blanusa et al 2005;Meir et al 2010;Xie et al 2013), which was further demonstrated by our recent work (data not published).…”
Section: Introductionmentioning
confidence: 59%